2020
DOI: 10.1051/matecconf/202031205001
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Impact of Human Error in Maintenance of Mechanical Systems

Abstract: The concept of minimizing human error in maintenance is progressively gaining attention in various industries. The incorporation of human factors when solving engineering problems, particularly in maintenance, can no longer be ignored where high standards of performance are expected. The journey of improving maintenance performance through the reduction of human error begins with the understanding of causes and impact of human error in maintenance. This paper evaluates previous scholarly writings on human erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As mentioned above, the types of human factors related to incidents from maintenance personnel were refined and classified according to their significance, as shown in Table 3. The categories are divided according to the human factors in maintenance industry (Nkosi et al, 2020). The most frequent human factor in the results is the unreasonable work plan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the types of human factors related to incidents from maintenance personnel were refined and classified according to their significance, as shown in Table 3. The categories are divided according to the human factors in maintenance industry (Nkosi et al, 2020). The most frequent human factor in the results is the unreasonable work plan.…”
Section: Resultsmentioning
confidence: 99%
“…According to Reason (2000), in the analysis of human error, we should not only consider the "active failure" that is difficult for personnel to avoid. More importantly, however, the "latent condition" should be identified which is related to the loopholes in the organization or system, often related to the organization's F I G U R E 1 Causes of human error in the maintenance of mechanical systems (Nkosi et al, 2020). management and designers of the system in the organization.…”
Section: The Definition Of Human Error-related Accidents/incidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Cho's study also revealed that poor management and lack of standard processes were the main organizational factors of DE [69]. Moreover, many studies focusing on human error have emphasized organizational factors, particularly management obligation [70][71][72], resource allocation [73], and safety culture [74].…”
Section: Discussionmentioning
confidence: 99%
“…Since the written procedures are sometimes long and experts prefer to rely on their experience and skills, “procedures usage” is recognized as the leading factor in this study. A review of the literature in the maintenance of mechanical systems showed that the causes of human error were poor management and supervision, organizational culture, incompetence, poor procedures, poor communication, time pressure, plant and environmental conditions, and poor work design 38 . Risk factors at different levels of technical, human, organizational, and environmental factors are presented in Refs.…”
Section: Identification Of the Human Error Roots In The Maintenance Groupsmentioning
confidence: 99%